Sistem Tataniaga Kentang di Kecamatan Hatu-Builiko, Kabupaten Ainaro, Timor Leste - Freitas, Boaventura Antonio Cardoso; Darmawan, Dwi Putra; Adi Putera, IG. Setiawan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2014)
Marketing system in important part in agribusiness system with forming connectivity of agriculture produck from farmer’s to the final consumer. The marketing system wil influence product purchasing including divides of benefit. Use of descriptive method Analysis in this research is aims to clarify how are the potato producing in Hatu-Builiko Sub-District delivery to the market consume. The purpose of the research to determine how far the channel marketing involve, how’s the marketing function applied to the condition of the market and which marketing channel mostly  efficient trough margin marketing and farmer share. The sample of location and sample of farmer were selected by purposive sampling method; and the sample of trades was selected trough snowbowling sampling method. The number of farmer’s was selected 20 peoples and the number of trades was selected fourteen peoples.the technical coleteing data was by observation and direct interview. The research conducted in Hatu-Builiko Sub District at Ainaro District of Timor Leste. The result, there were three channel of marketing applied, mostly the three marketing channel function were selling potatoin Ainaro District market. Market structure was conducted as monophony for the farmer’s, monopoly for the trade collector and free competition for the retailer and wholesalers. The market behavior was elaborate in good way between farmer’s and trade collector and either between trade collector and retailer and also trade collector and wholesalers. The payment procedure was cash based. The most efficient marketing channel wascontributing the best value as the result of margin marketing and farmer share which is was third marketing channel.
Keywords: marketing channel. market structur, margin and farmer’s share